Penerapan Metode RUP dalam Pengembangan Sistem Informasi Kepegawaian pada PT CNMG - Kennedy, Felix; Elizabeth, Triana (MDP Student Conference, 2025)
This research was conducted at PT China National Machinery Group, the reason for this research is that there are problems in the company that can be resolved through a personnel information system that functions as a system related to data and needs for employees. At PT. China National Machinery Group still has several problems with the existing staffing system such as companies having difficulty accessing application files from prospective employees, permission forms and doctor's letters are not recorded properly and correctly, employee absence data is quite often not recorded properly and correctly, employee data can be accessed by unauthorized people, admin staff must manually calculate the number of employee absences based on the monthly attendance file which takes longer time. The methodology used to develop the system is the RUP (Rational Unified Process) method, while the tools used are Visual Studio Code, XAMPP, MySQL, and Laravel Framework. The results of making this application are expected to help PT. China National Machinery Group in overcoming existing problems such as in the employee recruitment process, attendance process, leave process, sickness, promotion, demotion, termination, employee data, attendance data and assignments to company employees.